Analysis of The Demographic Characteristics of The Community And Patterns of Use Of Antibiotic Processing Methods In Kebonagung Village, Demak - Nauval Alfarizi; Ahmad Suriyadi Muslim; Intan Adevia Rosnarita (International Journal of Health and Pharmaceutical (IJHP), 2025)
Irrational antibiotic use remains a serious challenge in efforts to control bacterial resistance globally. One form of this irrational use is the purchase of antibiotics without a prescription, which is still widespread in various regions, including rural areas such as Kebonagung Village, Demak Regency. Lack of supervision and community demographic characteristics also influence antibiotic acquisition methods. This study aims to determine the relationship between demographic characteristics and antibiotic use patterns on antibiotic acquisition methods in the community of Kebonagung Village. The research method used was an observational analytic study with a cross-sectional design. A total of 118 respondents were selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using the Chi-square test with a significance level of 0.05. The analysis results showed a significant relationship between age (p = 0.011), education level (p = 0.015), and type of employment (p = 0.006) with antibiotic acquisition methods. Gender did not show a significant relationship (p = 0.138). The use pattern in this study was defined limitedly based on the type of antibiotic used according to the WHO AWaRe classification, as well as the reasons for antibiotic use based on perceived symptoms. The type of antibiotic based on the WHO AWaRe classification showed a significant relationship with the method of antibiotic acquisition (p = 0.001), with the finding that Access category antibiotics were more often obtained without a prescription, while the Reserve category was entirely obtained with a prescription. The analysis showed that there was no significant relationship between the reason for antibiotic use based on perceived symptoms and the method of antibiotic acquisition (p = 0.616). The results showed that age, education level, occupation, and type of antibiotic showed a significant relationship with the method of antibiotic acquisition, while gender and the reason for antibiotic use based on perceived symptoms did not show a significant relationship. These findings can be the basis for developing educational interventions to increase public awareness of how to obtain appropriate antibiotics, in order to prevent inappropriate access and support resistance prevention efforts at the community level.